IMPLEMENTATION OF EXISTENTIAL COUNSELING TECHNIQUE IN OVERCOMING QUARTER LIFE CRISIS PROBLEMS IN ADOLESCENTS IN SURABAYA - Hikmal Putra Maulana; Muhammad Affifudin Ghozali; Dela Febiyanti; Tasha Haty Fajar; Karina Putri Ramadhani (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
Quarter life crisis is a psychological phenomenon often characterized by feelings of confusion, anxiety and uncertainty about life goals, career and social relationships. This phenomenon often occurs in adolescents who are in two phases of transition to adulthood. One approach that can be used to overcome this problem is the existential approach. This approach focuses on achieving higher self-awareness, which is important in overcoming existential crises such as quarter life crisis. This study aims to explore the effectiveness of using existential counseling techniques in helping adolescents overcome quarter life crisis. Through a qualitative method with a case study design presented in a descriptive narrative, this research shows that the existential approach can have a positive impact in increasing self-understanding, clarifying life goals, and helping individuals accept the uncertainties and challenges they face.